2023
DOI: 10.1186/s40001-023-01404-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the degree of disability in patients with neuromyelitis optica spectrum disorders

Lili Shi,
Dawei Li,
Yunxiu Zhang
et al.

Abstract: Objective To investigate the factors influencing the degree of disability in patients with neuromyelitis optica spectrum disorder (NMOSD) and provide evidence for disease monitoring and clinical intervention. Methods Eighty-four patients with NMOSD at Xuanwu Hospital Capital Medical University were enrolled in this retrospective study. Before treatment, blood was collected from all patients, and their expanded disability status scores were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…26 In a recent study by Shi et al, NMOSD patients were divided into mild/moderate disability and severe disability groups according to their EDSS score, and some of the patients were in remission. 27 The results demonstrated that total bilirubin was an independent factor that influenced the severity of disability. Besides, albumin was closely related to NMOSD severity.…”
mentioning
confidence: 92%
“…26 In a recent study by Shi et al, NMOSD patients were divided into mild/moderate disability and severe disability groups according to their EDSS score, and some of the patients were in remission. 27 The results demonstrated that total bilirubin was an independent factor that influenced the severity of disability. Besides, albumin was closely related to NMOSD severity.…”
mentioning
confidence: 92%